2015
DOI: 10.31768/2312-8852.2015.37(3):218-222
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine, Folate and Vitamin B12 Levels in Patients With Lung Cancer

Abstract: Aim: Disorders in the metabolism of homocysteine and B vitamins, which are involved in a one-carbon transfer reaction and important for DNA synthesis and methylation, have been hypothesized to be associated with carcinogenesis. The purpose of this study is to evaluate the levels of homocysteine, vitamin B12 and folic acid in patients with newly diagnosed lung cancer and determines whether they might be used as an accurate tumor marker for monitoring the patients if they are found to be elevated in lung cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Results of our retrospective study suggest that serum folate concentration is inversely associated with lung cancer diagnosis. This is consistent with the EPIC cohort, one retrospective study and meta-analysis [9, 13, 19]. The mean folate concentration in our study was 22.52 nmol/l in controls, what is higher in comparison to that reported in all other analyses (14.4 nmol/l in EPIC [13], 4.3 ng/ml (9.7 nmol/l) in Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study [14], and 6.1 pg/ml [9] and 7.8 ng/ml (17.7 nmol/l) [10] in retrospective studies).…”
Section: Discussionsupporting
confidence: 90%
“…Results of our retrospective study suggest that serum folate concentration is inversely associated with lung cancer diagnosis. This is consistent with the EPIC cohort, one retrospective study and meta-analysis [9, 13, 19]. The mean folate concentration in our study was 22.52 nmol/l in controls, what is higher in comparison to that reported in all other analyses (14.4 nmol/l in EPIC [13], 4.3 ng/ml (9.7 nmol/l) in Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study [14], and 6.1 pg/ml [9] and 7.8 ng/ml (17.7 nmol/l) [10] in retrospective studies).…”
Section: Discussionsupporting
confidence: 90%
“…Malnutrition is common in patients with advanced cancer despite their commonly normal body mass index [ 75 ]. Such patients are at risk of subclinical deficiencies of other micronutrients [ 22 ], as was demonstrated in this study with regard to vitamin C. It is reasonable to presume that normal status with regard to all vitamins and essential minerals, not just certain selected ones, will provide the best outcomes. Future controlled clinical trials testing the benefits of correcting micronutrient deficiencies in people with advanced cancer should use a combination of micronutrient supplements that target documented subclinical deficiencies, in addition to optimal standard symptom management.…”
Section: Discussionmentioning
confidence: 82%
“…As a secondary objective, we tested the ability of three questionnaires to measure mood, well-being, and cancer-related symptoms in the context of vitamin D loading. More than one subclinical micronutrient deficiency can occur in a patient with cancer [ 22 ]. To explore this possibility, we measured plasma vitamin C concentrations in the study participants.…”
Section: Introductionmentioning
confidence: 99%
“…182,183 In addition to these injuries, RIC can also protect the lung from direct IRI as determined by improved lung functions, oxygenation capacity, and reduced pulmonary hypertension. 184 Although, multiple studies showed that high plasma Hcy concentration is related to the severity of lung impairment, [185][186][187] however, whether RIC could impart protective effects on pulmonary tissue has not been done during HHcy mediated lung injuries.…”
Section: Lungmentioning
confidence: 99%